решите уравнение: 6,3-(5,6x+2,7)=0,6-0,4x 2)5.4-7x=-0.9+2x вынесите общи множитель за скобки: 4ax-12ay+36az

1

Ответы и объяснения

2014-02-02T20:21:14+04:00
 6,3-(5,6x+2,7)=0,6-0,4x    6,3-5,6X - 2,7 = 0,6 - 0,4X         3,6 - 5,6X = 0,6 - 0,4X
3,6 - 0,6 = 5,6X - 0,4X              3 = 5,2X    X = 3/5,2     X = 3: 52/10  X = 3:52*10=15/26
X=15/26

     2)5.4-7x=-0.9+2x       5,4 +0.9=2X+ 7X     6,3 = 9X      X=0,7
                   
 вынесите общий множитель за скобки: 4ax-12ay+36az = a(4x - 12y +36z)